Drug shortages in Israel, revisited: a bitter pill to swallow - Eyal Schwartzberg; Eli Marom; Alla Vishkautzan; Einat Gorelik; Segev Shani (Israel Journal of Health Policy Research, 2024)
Abstract Background In 2017, we published an article addressing drug shortages (DS) in Israel, exploring regulatory perspectives, challenges, and potential solutions. Since then, DS remain a significant concern for patients, healthcare providers, and policymakers globally. In this updated article, we revisit the topic, providing new insights, data, and analysis on the current DS landscape in Israel, efforts to mitigate them, and propose strategies to combat this escalating issue. Methods We conducted a comprehensive search of the Israeli Ministry of Health (MOH) DS database, spanning from 2014 to the present. We extracted DS numbers and their reasons. Further searches on the Israeli MOH website, pharmaceutical division archives, and the internet yielded official MOH publications and correspondence regarding regulatory responses to DS from 2017 onwards. Additionally, two specific cases of DS were examined to analyze their handling. Recent activities and publications from the Israeli MOH aimed at reducing DS were also reviewed. Results Between 2014 and 2022, DS surged 2.66-fold. Total DS were 3228; 672 due to commercial reasons, and 2556 to operational reasons (20.5% and 79.5% respectively). The average duration of intermittent DS increased 1.56-fold, from 85 to 133 days. Manufacturers informed the MOH 22 days prior to actual shortage on average. Analyzing 2022's DS (640) by ATC groups, prominent categories included nervous system drugs (18%), drugs acting on the alimentary tract and metabolism (14%), and dermatologicals (11%). Operational DS in 2022 (n = 564) were primarily due to stock delivery delays (38%), stock over-utilization (12%), and raw material shortages (9%). Sixteen official MOH publications on DS were identified from 2017 onwards. Moreover, two high-impact DS case studies were examined. Conclusion Despite routine monitoring by the Israeli MOH and updating the DS policy throughout this period, DS persist, intensifying annually and posing serious health risks. This trend mirrors international patterns, affecting countries globally. In Israel's uniquely structured healthcare system, with its swift stakeholder cooperation and implementation capabilities, more effective DS management is conceivable. We propose ten universally applicable rules to address DS challenges.